Voltage Differencing Buffered Amplifier-Based Novel Truly Mixed-Mode Biquadratic Universal Filter with Versatile Input/Output Features - Mohammad Faseehuddin; Norbert Herencsar; Sadia Shireen; Worapong Tangsrirat; Sawal Hamid Md Ali (My University, 2022)
In this paper, a first-of-a-kind mixed-mode universal filter employing three VDBAs and three passive components, is proposed. The filter operates in all four modes and provides all five filter responses, namely voltage-mode (VM), current-mode (CM), trans-impedance-mode (TIM), or trans-admittance-mode (TAM). Additionally, the same filter topology can also work as a CM single-input-multi-output (SIMO) filter. A state-of-the-art comparison of various ‘voltage differencing’ variants of the voltage differencing buffered amplifier (VDBA)-based SIMO/MISO (single-input-multi-output/multi-input-single-output)-type biquad filters further highlight the significance of the presented research. In the proposed no passive component matching is required for generating the filter responses. The filter circuit also provides inbuilt tunability of the quality factor independent of the pole frequency. The non-ideal frequency dependent gain and component sensitivity analyses of the filter were also performed. The Silterra Malaysia 0.18μm process design kit (PDK) is employed to design and validated the proposed VDBA-based filter using the Cadence design software. The simulation results closely follow the theoretical predictions. To further verify the practical feasibility of the proposed filter, an experimental evaluation is also completed. The VDBA-based filter is implemented using off-the-shelf operational transconductance amplifiers Intersil CA3080, Texas Instruments LF356 op-amp, and Analog Devices AD844s. The filter is designed for a characteristic frequency of 100 kHz. The time and frequency domain measurement results indicate the proper functioning of the filter.
Keywords: All-pass filter; Voltage-controlled filter; Digital biquad filter; Butterworth filter; Electronic filter topology; Constant k filter; Analog and Mixed-Signal Circuit Design